Revisiting The Dynamics Of Gender-Based Development: An Approach to Development Studies - Elmira Mufliha Camila (EcceS (Economics, Social, and Development Studies), 2021)
The Gender Development Index in Indonesia and East Java 2019 is still below the world and national average. This shows that the equality of development between male and female in East Java is still lagging behind other provinces. The novelty of this research is trying to revisit the issue of the Gender Development Index (GDI) in East Java. This research aims to analyze the effect of Gross Regional Domestic Product (GRDP), poor population, and Labor Force Participation Rate (LFPR) on the Gender Development Index (GDI) in East Java partially and simultaneously. This research uses quantitative research methods with panel data regression analysis techniques. The data used in this research is secondary data obtained from the Central Bureau of Statistics in East Java during 2017-2019. The results of this research showed that the GRDP variable and poor population variable have a negative and significant effect on the Gender Development Index. Meanwhile, the LFPR variable has an insignificant and positive effect on the Gender Development Index. In addition, simultaneously the variable of GRDP, poor population, and LFPR has a significant effect on the Gender Development Index. Currently, there is still a gap between the roles of men and women. The role of women is still not optimally utilized because women's resources in the fields of health, education, and the workforce are still low. But this can be overcome if there is an increase in the labor productivity of both male and female residents so the income of the population will also increase and the number of poor people decreases. The implication of this research is the role of all parties, especially the government, is needed to pay more attention to and increase population growth and reduce poverty levels to increase gender equality in East Java. Keywords: GRDP; Gender Development Index; Poverty